O tempo das águas: ciclos de vida entre as margens do rio São Francisco, a Ilha das Pimentas - Pirapora/MG - Souza, Angela Fagna Gomes de (2011)
An interactive research is the perspective that guided that work, walking between geography and anthropology. That proposal becomes from the need of other views, launching a curious, penetrating glance, opened to different meanings, linking knowledge and people, places and information. As empirical reference the investigation locus is the Pimentas Island located in São Francisco river, in Pirapora-MG proximities. Along the researches the behavior and memory of the people who lived in the island were marked by interaction between investigator and investigated, watching the other in their own living place. I looked for analyze the knowledge of the Pimentas Island residents, searching as main objective to understand and identity, ways of life and work of these people who works and lives on the island. Living in the simplicity of everyday life in their small lots, the residents transform this place in a mosaic of culture, with multiple meanings that can be translated in a dynamic community life. Their experience is unique, marked by a deep knowledge about the nature rules and a feeling of affection of these people, the São Francisco river, its waters and the island, their welcome place.